Chronic obstructive pulmonary disease: Signs and symptoms, diagnosis, treatments, lifestyle risk factors and management - Lim, Sook Yee; Ulaganathan, Vaidehi; Gunasekaran, Baskaran; Salvamani, Shamala; Tiong, Yee Lian; Muhammad Royani, Siti Madihah; Silvermany, Kughaneshwary; Augundhooa, Digsha; Chambari, Mahla (Life Sciences, Medicine and Biomedicine, 2024)
Chronic Obstructive Pulmonary Disease (COPD) is associated with increased health complications, leading to a rise in mortality rates. COPD remains a significant global health issue, underscoring the importance of recognizing symptoms, facilitating diagnosis, and implementing effective treatment strategies. However, information on lifestyle risk factors and the management of COPD remains fragmented. This review paper aims to understand the clinical pathophysiologic changes triggered by lifestyle practices and their management strategies. It is important to understand its symptoms, diagnostics criteria, and treatment to correlate with lifestyle risk factors and to identify effective lifestyle interventions. Lifestyle practices as defined by dietary practices such being anorexia and low fruit and vegetable intake, smoking habits, alcohol consumption, and physical inactivity have increased the risk of COPD. This review suggested lifestyle approaches for COPD treatment such as regular exercise, a healthy diet, and avoiding smoking. In this case, the development of the guided improved intervention is important for a better understanding of the mechanisms between COPD and its associated lifestyle practices. This information may help clinicians, health practitioners, and dietitians to guide patients to implement improved dietary interventions. To avoid the progression of COPD, lifestyle practice therapy could be the most effective strategies that aid with medications as prescribed by the physicians.